Perancangan Sistem Monitoring Power BTS (Base Transceiver Station) Menggunakan SMS Gateway Berbasis Mikrokontroler ATMega 8535 - Auliq, M A'an (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2019)
Power system at BTS (Base Transceiver Station) plays an important role in supplying power to all devices that’s supporting signal processing. But the power system needs its own surveillance, especially during the power outage, especially the electricity. The problems that are often experienced by the base stations, especially in areas of high levels of electrical outages. Based on this  idea researcher design and create a monitoring tool power base stations using Atmega microcontroller-based SMS gateway 8535. This system aims to supervise / monitor the condition of the power system at BTS when disruptions, the system uses a voltage sensor as an indicator of disturbance and SHT11 sensor as a parameter measurement of temperature and humidity of the room. This is connected to the SMS Gateway using RS-232 communications and controlled using a microcontroller Atmega8535.Data SDYhttps://materassomemory.org/https://visualresearchnetwork.org/https://brazoriafumc.org/https://atmamayor.com/https://viralblasts.com/Bloom ScapeRokokbetRokokbetScatter HitamRokokbethttps://press.umam.edu.my/Rokokbethttps://theusajournals.com/RokokbetShiowlaRokokbetRokokbetRokokbetRokokbetRokokbetShiowla